Nutrition and quality of maize - Okoruwa, A.; Kling, J. (1996)
Maize is a major cereal crop. Worldwide, wheat, maize, and rice are produced in greater quantities than any other crop. Of these crops, maize has the highest average yield per hectare. Maize is a good source of energy for both humans and animals. It is high-yielding, easy to process and readily digested. Maize is deficient in lysine and tryptophan, however, consumption with a legume improves protein quality in the diet. The oil is of good quality. Varieties differ in physical and chemical properties of the grain, which affects their suitability for various end uses.